Effect of fluctuating hot temperatures on performance and immunity in finishing pigs - M A Jensen; Frank Blecha; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1983)
Housing pigs in a thermal stress environment reduced gain, intake and feed efficiency. Cell mediated immunity responses were lower under the constant heat stress as well as when the temperature was lowered to a thermal neutral temperature for only 4 hours daily. Daily cooling to thermal neutral for 4, 8, or 16 hours improved growth performance. Antibody responses were not altered by temperature fluctuations.; Swine Day, Manhattan, KS, November 10, 1983
Keywords: Swine day; 1983; Kansas Agricultural Experiment Station contribution; no. 84-174-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 442; Swine; Fluctuating hot temperatures; Peformance; Immunity